2012
DOI: 10.1258/jrsm.2011.110223
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial behaviour in children with and without callous-unemotional traits

Abstract: SummaryMore than 15 years of research have documented behavioural differences between callous-unemotional and non-callous subtypes of children with antisocial behaviour. Recent studies also suggest that children with callous-unemotional traits may be genetically vulnerable to antisocial behaviour, while those without callous-unemotional traits appear to have primarily environmental aetiology to their antisocial behaviour. Furthermore neurocognitive profiles differ between antisocial children with and without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 36 publications
6
84
5
Order By: Relevance
“…Disruptions in perceptions of threat are common in conduct disorder and ODD. (64, 65) This is primarily true for cases in which symptoms are associated with negative developmental environments but not genetic risk or callous-unemotional traits. (66) It is possible that persistent threat appraisals paired with low confidence in one’s capabilities and dysregulated physiological responses increase risk for reactive forms of aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in perceptions of threat are common in conduct disorder and ODD. (64, 65) This is primarily true for cases in which symptoms are associated with negative developmental environments but not genetic risk or callous-unemotional traits. (66) It is possible that persistent threat appraisals paired with low confidence in one’s capabilities and dysregulated physiological responses increase risk for reactive forms of aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Callous-unemotional traits, characterized by low empathy, callousness, and low interpersonal emotions, identify youth with severe, chronic, and stable antisocial behavior (8). Studies demonstrating distinct neural correlates and higher heritability of antisocial behavior in the presence of callous-unemotional traits suggest different etiological pathways to antisocial behavior with, versus without, callous-unemotional traits (9-11). However, as most research on callous-unemotional traits has focused on late childhood and adolescence, we know little about the developmental origins of callous-unemotional traits.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with conduct problems and callous-unemotional traits show less amygdala responsiveness to fearful faces (but not other emotional expressions) compared to healthy controls [72][73][74][75] and compared to children with conduct problems but low CU traits [76]. Functional imaging studies of children and adolescents have also found youths with both conduct problems and either psychopathic traits exhibit lower right amygdala activity during an afective theory of mind task [77].…”
Section: Neurobiological Factorsmentioning
confidence: 98%